Does surface wettability influence the friction and wear of large-diameter CoCrMo alloy hip resurfacings?. (August 2013) - Curran, Sarah; Hoskin, Tom; Williams, Sarah; Scholes, Susan C; Kinbrum, Amy; Unsworth, Anthony
The role of surface tension in the lubrication of metal-on-metal (CoCrMo alloy) hip resurfacings has been investigated to try to explain why all metal joints fail to be lubricated with simple water-based lubricants (sodium carboxymethyl cellulose), which have similar rheology to synovial fluid, but are lubricated with the same fluid with the addition of a proportion of bovine serum. As part of this study, surfactants, in the form of detergents, when added to carboxymethyl cellulose, have been shown to produce a predominantly fluid-film lubrication mechanism with friction even lower than the biological lubricant containing serum. Friction factors were reduced by 80% when a detergent was added to the lubricant. It is considered that the failure of the water-based fluids to generate fluid-film lubrication is due to the fact that 'boundary slip' takes place where the fluid does not fully attach to the bounding solid surfaces as assumed in Reynolds' equation, thereby drawing in less lubricant than predicted from hydrodynamic theory. The addition of surfactants either in the form of natural materials such as serum or in the form of detergent reduces surface tension and helps the water-based lubricant to attach more fully to the bounding surfaces resulting in more fluid entrainment and thicker fluid-film formation. This was confirmed by up to 70% lower wear being found when these joints were lubricated in a detergent solution rather than 25% bovine serum.